Análise financeira de investimento em sistema fotovoltaico on grid na modalidade microgeração distribuída em Parintins-AM - Silva, Valdelírio Miranda (Brasil, 2023)
The present work is a study of the conclusion of a course in administration that aims to analyze the financial viability of the microgeneration market distributed in photovoltaic energy on grid, by companies that use the system, in the city of Parintins, in the interior of the state of Amazonas, serving as a source of research for enterprises that wish to join the photovoltaic sector, including those that are in the process of consolidation. For this, a descriptive market research was carried out with a quantitative and exploratory approach, through the application of questionnaires with companies that consume this service. Payback, Net Present Value (NPV) and Internal Rate of Return (IRR) were the economic viability indicators applied to the financial data collected. From such analyses, the viability of investing in the photovoltaic sector was verified, since a positive NPV and an IRR higher than the existing forms of investments in the financial market were found, which implies that the investment is considered attractive because it presents revenues greater than the expenses.